ANALISIS KETERLAKSANAAN PEMBELAJARAN JARAK JAUH MATA PELAJARAN MATEMATIKA DI KELAS TINGGI SEKOLAH DASAR PADA MASA PANDEMI COVID-19 - Dyoty Auliya Vilda Ghasya; Asmayani Salimi; Rio Pranata (Jurnal Numeracy, 2021)
The research aims to describe the learning planning of Mathematics subjects that have been made by teachers in grade IV, V and VI elementary schools, describing the pattern of implementation of distance learning in mathematics subjects grade IV, V and VI elementary school, describing the difficulty of teachers in carrying out distance learning in mathematics subjects grade IV, V and VI elementary school , describe the difficulties of grade IV, V and VI elementary school students in following distance learning in Mathematics subjects, describe the advantages of the implementation pattern of distance learning in mathematics grade IV, V and VI elementary school, and describe the opinions of parents or guardians of students on distance learning of Mathematics subjects grade IV, V and VI elementary school during the COVID-19 pandemic. This study uses qualitative research approach with exploration study type. The result of this study is distance learning in mathematics subjects grade VI, V and VI elementary schools there are conducted online and mixed. The implementation of distance learning in mathematics subjects grade VI, V and VI received a variety of responses from teachers, students and parents or guardians. Abstrak Penelitian bertujuan untuk mendeskripsikan perencanaan pembelajaran mata pelajaran Matematika yang telah di buat oleh guru pada kelas IV, V dan VI sekolah dasar, mendeskripsikan pola pelaksanaan pembelajaran jarak jauh mata pelajaran Matematika kelas IV, V dan VI sekolah dasar, mendeskripsikan kesulitan guru dalam melaksanakan pembelajaran jarak jauh pada mata pelajaran Matematika kelas IV, V dan VI sekolah dasar, mendeskripsikan kesulitan siswa kelas IV, V dan VI sekolah dasar dalam mengikuti pembelajaran jarak jauh pada mata pelajaran Matematika, mendeskripsikan kelebihan pola pelaksanaan pembelajaran jarak jauh mata pelajaran Matematika kelas IV, V dan VI sekolah dasar, dan mendeskripsikan pendapat orang tua atau wali murid terhadap pembelajaran jarak jauh mata pelajaran Matematika kelas IV, V dan VI sekolah dasar pada masa pandemi COVID-19. Penelitian ini menggunakan pendekatan penelitian kualitatif dengan jenis studi eksplorasi. Adapun hasil dari penelitian ini adalah pembelajaran jarak jauh pada mata pelajaran matematika kelas VI, V dan VI sekolah dasar ada yang dilaksanakan secara online maupun campuran. Pelaksanaan pembelajaran jarak jauh pada mata pelajaran matematika kelas VI, V dan VI mendapatkan berbagai respon dari guru, siswa dan orang tua atau wali murid. Kata Kunci: Pembelajaran Jarak Jauh, Matematika, Kelas Tinggi Sekolah Dasar